Approximation Characteristics of the Spaces S_p^ϕ in Different Metrics - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We continue the investigation of the approximation characteristics of the spaces S_p^ϕ introduced earlier. In particular, we establish direct and inverse theorems on the approximation of elements of these spaces. We also determine the exact values of upper bounds of m-term approximations of q-ellipsoids in the spaces S_p^ϕ in the metrics of the spaces S_p^ϕ.